Contributory Factors in Traffic Congestions in the 2nd District of Albay, Philippines: Basis for Traffic Management Framework - Balla, Domingo; Macabeo, Manny (JPAIR Multidisciplinary Research, 2023)
The global concern over traffic safety conditions has escalated due to the growing number of vehicles and pedestrians. Governments are putting significant efforts into implementing systems to alleviate and reduce traffic congestion. This study aimed to identify the factors contributing to traffic congestion in the 2nd district of Albay through quantitative research. It examined traffic congestion status in terms of Data Traffic Volume, Rush Hour, Classification of Vehicles, and Road Users. The research pinpointed key contributors to congestion, including insufficient road infrastructure, high vehicle density, rapid population growth, poor public transport, and road quality. A survey questionnaire was administered to personnel from Camalig MPS, Daraga MPS, and Legazpi City Police Station, as well as Public Safety Officers from the mentioned areas. The community, representing riders and commuters in the Poblacion area, also participated. The findings revealed that traffic congestion is prevalent in the 2nd district of Albay, primarily driven by traffic volume, rush hour, vehicles, and road users. As a result, the study emphasizes the need for a standardized traffic management framework to be implemented. This framework aims to coordinate stakeholders’ perceptions regarding the factors contributing to traffic congestion, serving as a guide for effective traffic management in the region.